Genetic Susceptibility to Fungal Infections and Links to Human Ancestry - Naik, Bharati; Ahmed, Sumayyah M. Q.; Laha, Suparna; Das, Shankar Prasad (Frontiers in Genetics, 2021)
Over the ages, fungi have associated with different parts of the human body and established symbiotic associations with their host. They are mostly commensal unless there are certain not so well-defined factors that trigger the conversion to a pathogenic state. Some of the factors that induce such transition can be dependent on the fungal species, environment, immunological status of the individual, and most importantly host genetics. In this review, we discuss the different aspects of how host genetics play a role in fungal infection since mutations in several genes make hosts susceptible to such infections. We evaluate how mutations modulate the key recognition between the pathogen associated molecular patterns (PAMP) and the host pattern recognition receptor (PRR) molecules. We discuss the polymorphisms in the genes of the immune system, the way it contributes toward some common fungal infections, and highlight how the immunological status of the host determines fungal recognition and cross-reactivity of some fungal antigens against human proteins that mimic them. We highlight the importance of single nucleotide polymorphisms (SNPs) that are associated with several of the receptor coding genes and discuss how it affects the signaling cascade post-infection, immune evasion, and autoimmune disorders. As part of personalized medicine, we need the application of next-generation techniques as a feasible option to incorporate an individual’s susceptibility toward invasive fungal infections based on predisposing factors. Finally, we discuss the importance of studying genomic ancestry and reveal how genetic differences between the human race are linked to variation in fungal disease susceptibility.